Biologia de Anofelinos Amazônicos. XIII. Estudo do ciclo biológico de Anopheles nuñez-tovari Gabaldon, 1940 (Diptera, Culicidae) - Scarpassa, Vera Margarete; Tadei, Wanderli Pedro (Acta Amazonica, 1990)
In a study of the developmental cycle of Anopheles nuñez-tovari, 108 egg hatches with a total of 13.999 eggs were analyzed. The mean number of eggs per hatch was 128, 83 4,85 and there was a high eclosing rate of 84,06%. 89% out of the total number of eggs that ecloded within 240 hours, did so within the first 48 hours with a mean time of 1,86 + 0,004 days. The mean number of eclosions per hatch was 109,39 + 5,26. The proportion of eggs ecloding is positively correlated with the number of eggs per hatch. However, when eggs hatches are grouped in class intervals of 40 eggs there is no correlation for some of them. The developmental time of larval stages varied, the longest being the fourth (pre-pupal) stage with a mean of 3,15 + 0,03 days. The shortest mean interval was from the second to third instar (mean 1,46 + 0,02 days). Itermediate values were observed for the stages 1st + 2nd instar, 3rd - 4th instar and pupal-adult instar (2,34 + 0,02; 1,67 + 0,02 and 1,54 + 0,01 days, respectively). The mean developmental time from oviposition to adult emergencewas 12,02 + 0,004 days. The highest mortality was observed in the fourth larval (19,6%) and pupal (6,0%) stages. 71,4% of first instar larvae reached the adult stage, which is a high survival compared to previoous reports. The developmental time of A. nuñez-tovari appears to be closer to that of A. darlingi than A. triannulatus.